Successful transcatheter arterial embolization for massive hemorrhage from acquired uterine arteriovenous malformation which occurred as a complication of hysterectomy: A case report - Oh, Chang Hoon (Medicine (Baltimore), 2021)
RATIONALE: Uterine arteriovenous malformation (UVM), which can be congenital or acquired, is a relatively rare disorder that can cause life-threatening hemorrhage. Acquired UVM occurs predominantly after previous uterine procedures; rarely, it may occur after a hysterectomy. Although the best treatment option for UVM remains controversial, transcatheter arterial embolization (TAE) has recently been introduced as a safe and effective treatment. PATIENT CONCERNS: A 34-year-old woman who underwent hysterectomy for uncontrolled postpartum bleeding continued to have hemoperitoneum. DIAGNOSIS: Two days after surgery, massive hemoperitoneum was identified on computed tomography scan, and acquired UVM was diagnosed by angiography. INTERVENTIONS: The patient was successfully treated using TAE with an n-Butyl cyanoacrylate. OUTCOMES: After embolization, hemodynamic stability was achieved. A day after embolization, hemoglobin was 10.2 g/dL, and the patient was discharged from the hospital 4 days thereafter. LESSONS: Although the overall incidence of acquired UVM after hysterectomy is low, bleeding from acquired UVM should be considered as one of the differential diagnoses in the immediate postpartum period, especially when the clinical symptoms do not correlate with the amount of blood loss. A high index of suspicion, prompt diagnosis and intervention, and a multidisciplinary approach in the management were the elements of a successful outcome in this case.